Role of Research in Indian Education Sector in Modern India: Addressing Research Challenges in Indian Education Sector (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Education has attained a key position in the knowledge society both at national and worldwide dimension also. In the course of the most recent two decades, India has amazingly transformed its advanced education landscape. It has made boundless access to minimal effort brilliant college education for understudies everything being equal. With well-arranged extension and an understudy driven learning-driven model of education, India has bettered its enrollment numbers as well as has dramatically enhanced its learning results. India has had the capacity to resolve the longstanding tension among magnificence and equity. India has additionally attempted substantial scale reforms to better personnel understudy proportions by making showing an attractive profession way, growing limit with regards to doctoral understudies at research colleges and de-linking educational qualifications from instructing eligibility. In any case, the challenges confronted are immense and extensive. Indian arrangement of education is described by various imperatives and research is one of the primary ones. Completing Research in India has various challenges, for example, nonappearance of intellectual stimulation, accentuation on repetition learning, lack of scientific hypothesis and base, insufficient information, lack of scientific knowledge, and preparing in Research Methodology.